2021
DOI: 10.4049/jimmunol.2100166
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal Tissue Residence Confers a Distinct Differentiation Program upon Memory CD8 T Cells

Abstract: Tissue-resident memory CD8 T cells (CD8 T RM ) are critical for maintaining barrier immunity. CD8 T RM have been mainly studied in the skin, lung and gut, with recent studies suggesting that the signals that control tissue residence and phenotype are highly tissue dependent. We examined the T cell compartment in healthy human cervicovaginal tissue (CVT) and found that most CD8 T cells were granzyme B + and TCF-1 . To address if this phenotype is driven by CVT tissue residence, we used a mouse model to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
(52 reference statements)
5
15
0
Order By: Relevance
“…5D ). CD8+ T cells, which robustly express GzmB in response to viral infection or immunization 36 , 74 , 75 , also expressed little to no GzmB in healthy mice (VT: 5.6%; dLN: .09%; Fig. 5E ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5D ). CD8+ T cells, which robustly express GzmB in response to viral infection or immunization 36 , 74 , 75 , also expressed little to no GzmB in healthy mice (VT: 5.6%; dLN: .09%; Fig. 5E ).…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, given their localization within mucosal sites, Tregs interact with local T cells 15 , 28 32 , including non-circulating tissue-resident memory T cells (Trm) 33 35 . Both CD4+ and CD8+ mucosal Trm are important controllers of local viral infections, including vaginal HSV-2 infection 33 , 36 40 . Therefore, muscoal STI vaccine design efforts are focused on eliciting robust Trm responses at the site of infection 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…2 ). CD103 + CD8 + T RM cells show long-term persistence in organs such as the brain, skin and cervicovaginal tissue 8 , 39 , 92 , despite the loss of their CD103 − counterparts. The extent to which these spatial and temporal restrictions can operate was dramatically illustrated by experiments that lodged CD103 + CD8 + T RM cells in a small patch of skin, thus confining effective protection to just that location while leaving the remainder of the torso under the inferior control of memory cells in the blood 8 , 63 .…”
Section: T Rm Cells In the Lungsmentioning
confidence: 99%
“…The increase in the CD8 T cells could reflect heightened immune surveillance at a steady state in the vaginal tissue, which is in perpetual contact with the external environment and serves as a barrier against invading pathogens. HSV-2 is an example of a local FGT infection, wherein shedding is recurrent and often frequent, yet is generally rapidly contained by a very low density of CD8 TRMs (20,(25)(26)(27)(28). Prior studies have characterized the protective role of CD8 TRM in the FGT (25)(26)(27)(28), and yet mathematical modeling revealed that in situations wherein HSV-2-specific CD8 TRM could only exert contact-mediated killing, viral spread was not contained (29).…”
Section: Introductionmentioning
confidence: 99%
“…HSV-2 is an example of a local FGT infection, wherein shedding is recurrent and often frequent, yet is generally rapidly contained by a very low density of CD8 TRMs (20,(25)(26)(27)(28). Prior studies have characterized the protective role of CD8 TRM in the FGT (25)(26)(27)(28), and yet mathematical modeling revealed that in situations wherein HSV-2-specific CD8 TRM could only exert contact-mediated killing, viral spread was not contained (29). Thus, we sought to investigate how memory T cells could participate in protection to local virus infection in an innate-like fashion in the FGT.…”
Section: Introductionmentioning
confidence: 99%